CEO Succession Mechanisms, Organizational Context, and Performance: A Socio‐Emotional Wealth Perspective on Family‐Controlled Firms. (15th September 2014) - Minichilli, Alessandro; Nordqvist, Mattias; Corbetta, Guido; Amore, Mario Daniele
Abstract This article extends the literature on CEO succession and financial performance by addressing corporate owners' mixed motives and desires to protect their interest in being in business. We draw on a Socio‐Emotional Wealth (SEW) perspective to investigate how the choice of one of three succession mechanisms – relay succession, 'horse races' among internal CEO candidates, and hiring from outside – may effectively balance trade‐offs between corporate owners' non‐financial SEW motives and the firm's financial performance. We find that implementing one of these succession mechanisms reduces the negative impact that typically characterizes CEO transitions in family firms. We also show that family presence on the board of directors offsets the benefits of having selected these balancing succession mechanisms, in either placing too much emphasis on SEW, or creating negative dynamics that make the chosen succession mechanisms less effective.